Photoconductive material for laser printing and method for preparing a photo drum thereof
Patent Information
- Application Number
- CN202310579426.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-22
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-05-22
AI Technical Summary
[0004]现有技术中所生产的OPC产品,液体配方不合理,导电材料、粘合材料、感光材料等分配不均匀,可能导致OPC感光度不够、电性能不达标,影响打印质量,从而使得所制备的产品无法满足客户要求
[0020]与现有技术相比,本发明的有益效果是:通过筛选合适比例的无机化合物以及导电高分子材料形成第一涂层,并通过筛选合适比例的酞箐类光导材料以及粘结性树脂材料形成第二涂层,另外,通过筛选合适比例的高分子树脂材料、导电树脂材料以及润滑剂形成第三涂层,所制备的光导材料具有良好的电性能,保存长久性较好,打印质量以及打印寿命较高。
Smart Images

Figure CN116841139B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of optical waveguide material preparation technology, and in particular to an optical waveguide material for laser printing and a method for preparing its photosensitive drum. Background Technology
[0002] With the rapid development of science and technology and the improvement of people's living standards, the types and quantities of office equipment are gradually increasing. As one of the office equipment, the printer is used to print the results of computer processing onto relevant media.
[0003] Organic photoconductor (OPC), also known as photoconductor drum, is a key consumable in laser printers. It is generally composed of a base material made of aluminum and a photosensitive material coated on the base material. The quality of the photoconductor drum largely determines the printer's print quality and maintenance costs.
[0004] The OPC products produced in the existing technology have unreasonable liquid formulations and uneven distribution of conductive materials, adhesive materials, and photosensitive materials, which may lead to insufficient photosensitivity and substandard electrical properties of OPC, affecting printing quality and making the prepared products unable to meet customer requirements. Summary of the Invention
[0005] Therefore, the purpose of this invention is to provide a photoconductive material for laser printing and a method for preparing the photosensitive drum thereon, so as to at least solve the shortcomings of the above-mentioned related technologies.
[0006] This invention proposes a photoconductive material for laser printing, comprising a first coating, a second coating, and a third coating. The first coating comprises 33-37% by mass of an inorganic compound and 63-67% by mass of a conductive polymer material, dispersed at a first particle size via nano-dispersion. The second coating comprises 35-45% by mass of a phthalocyanine photoconductive material and 55-65% by mass of an adhesive resin material, dispersed at a second particle size. The third coating comprises 32-38% by mass of a polymer resin material, 58-64% by mass of a conductive resin material, and 4% by mass of a lubricant, dispersed at a third particle size.
[0007] Furthermore, the first particle size is 200-300 nm, the coating thickness of the first coating is 3-6 μm, the inorganic compound includes any one of titanium dioxide, zinc oxide, and tungsten oxide, and the conductive polymer material includes any one of conductive nylon, polypropylene, and polypyrrole.
[0008] Furthermore, the second particle size is 1-2 μm, the coating thickness of the second coating is 0.8-2 μm, the phthalocyanine-based optical guide material includes any one of copper phthalocyanine, nickel phthalocyanine, zinc phthalocyanine, cobalt phthalocyanine, and iron phthalocyanine, and the adhesive resin material is any one of pure polyethylene and conductive PC.
[0009] Furthermore, the third particle size is 2-5 μm, the coating thickness of the third coating is 30-40 μm, and both the polymer resin material and the conductive resin material include any one of the following: polymer resin PC, polyethylene, polymer PAM, polyacrylamide, melamine, and formaldehyde resin.
[0010] Furthermore, the lubricant includes silicon dioxide.
[0011] This invention also proposes a method for preparing a photosensitive drum containing a photoconductive material, wherein the photoconductive material is the aforementioned photoconductive material, and the preparation method includes:
[0012] The inorganic compound, conductive polymer material, phthalocyanine photoconductive material, adhesive resin material, polymer resin material, conductive resin material, and lubricant are initially crushed and refined by the first mixer, and then ultrasonically crushed and refined by the second mixer to obtain the corresponding first liquid material, second liquid material, and third liquid material.
[0013] The first liquid material, the second liquid material, and the third liquid material are dispersed using a disperser with first dispersion parameters to obtain a first optical waveguide material, a second optical waveguide material, and a third optical waveguide material.
[0014] The first optical guide material is coated onto the OPC aluminum tube, and the coating is dried after coating the OPC aluminum tube to form the first coating.
[0015] The second optical guide material is coated onto the OPC aluminum tube, and the OPC aluminum tube is dried after coating to form the second coating.
[0016] The third photoconductive material is coated onto the OPC aluminum tube, and the OPC aluminum tube is dried after coating to form the third coating, so as to obtain a photosensitive drum containing the photoconductive material.
[0017] Furthermore, the first mixer is a V-type mixer, the second mixer is a multi-layer mixer, and the first dispersion parameters include a temperature of 20℃~40℃ and a dispersion time of 7 days.
[0018] Furthermore, the coating concentration range of the first, second, and third optical waveguide materials is 18–22 mol / L, and the coating viscosity range is 35–45 mol / L. When the coating thickness is 0.8 μm–1.2 μm, the coating speed is 1–1.2 mm / s; when the coating thickness is 6–7 μm, the coating speed is 2.6–2.8 mm / s; and when the coating thickness is 30–36 μm, the coating speed is 15–20 mm / s.
[0019] Furthermore, the drying process employs both low-temperature drying and high-temperature drying, with a drying time of 2.5–3 seconds. Specifically, the temperature range for low-temperature drying is 40–60°C, and the temperature range for high-temperature drying is 110–140°C. The OPC aluminum tube rotates at a first preset rotation speed during the drying process.
[0020] Compared with the prior art, the beneficial effects of the present invention are as follows: by screening an appropriate proportion of inorganic compounds and conductive polymer materials to form a first coating, and by screening an appropriate proportion of phthalocyanine photoconductive materials and adhesive resin materials to form a second coating, and by screening an appropriate proportion of polymer resin materials, conductive resin materials and lubricants to form a third coating, the prepared photoconductive material has good electrical properties, good long-term preservation, and high printing quality and printing life. Attached Figure Description
[0021] Figure 1 This is a flowchart of a method for preparing an optical guide material for laser printing according to a second embodiment of the present invention.
[0022] The following detailed description, in conjunction with the accompanying drawings, will further illustrate the present invention. Detailed Implementation
[0023] To facilitate understanding of the present invention, a more complete description will be given below with reference to the accompanying drawings. Several embodiments of the invention are illustrated in the drawings. However, the invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided so that this disclosure will be thorough and complete.
[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0025] Example 1
[0026] The first embodiment of the present invention provides a photoconductive material for laser printing, comprising a first coating, a second coating, and a third coating. The first coating comprises 33-37% by mass of an inorganic compound and 63-67% by mass of a conductive polymer material, and is dispersed to a first particle size by nano-dispersion. The second coating comprises 35-45% by mass of a phthalocyanine photoconductive material and 55-65% by mass of an adhesive resin material, and is dispersed to a second particle size. The third coating comprises 32-38% by mass of a polymer resin material, 58-64% by mass of a conductive resin material, and 4% by mass of a lubricant, and is dispersed to a third particle size.
[0027] In this embodiment, the first particle size is 200–300 nm, the coating thickness of the first coating is 3–6 μm, the inorganic compound includes any one of titanium dioxide, zinc oxide, and tungsten oxide, and the conductive polymer material includes any one of conductive nylon, polypropylene, and polypyrrole; the second particle size is 1–2 μm, the coating thickness of the second coating is 0.8–2 μm, the phthalocyanine photoconductive material includes any one of copper phthalocyanine, nickel phthalocyanine, zinc phthalocyanine, cobalt phthalocyanine, and iron phthalocyanine, and the adhesive resin material is any one of pure polyethylene and conductive PC; the third particle size is 2–5 μm, the coating thickness of the third coating is 30–40 μm, and both the polymer resin material and the conductive resin material include any one of polymer resin PC, polyethylene, polymer PAM, polyacrylamide, melamine, and formaldehyde resin.
[0028] Preferably, the first particle size is 300 nm, the coating thickness of the first coating is 6 μm, the inorganic compound is titanium dioxide with a mass percentage of 33%, and the conductive polymer material is conductive nylon with a mass percentage of 67%; the second particle size is 2 μm, the coating thickness of the second coating is 2 μm, the phthalocyanine photoconductive material is copper phthalocyanine with a mass percentage of 45%, and the adhesive resin material is pure polyethylene with a mass percentage of 55%; the third particle size is 5 μm, the coating thickness of the third coating is 40 μm, the polymer resin material is high-molecular-weight PC with a mass percentage of 32%, the conductive resin material is polyethylene with a mass percentage of 64%, and the lubricant is silicon dioxide with a mass percentage of 4%.
[0029] In summary, the photoconductive material for laser printing in the above embodiments of the present invention forms a first coating by selecting appropriate proportions of inorganic compounds and conductive polymer materials, a second coating by selecting appropriate proportions of phthalocyanine photoconductive materials and adhesive resin materials, and a third coating by selecting appropriate proportions of polymer resin materials, conductive resin materials and lubricants. The prepared photoconductive material has good electrical properties, good long-term preservation, and high printing quality and printing life.
[0030] Example 2
[0031] Please see Figure 1 In another aspect, the present invention also proposes a method for preparing an optical guide material for laser printing, wherein the optical guide material is the optical guide material in the above embodiment one, and the preparation method includes the following steps:
[0032] S201, the inorganic compound and conductive polymer material, phthalocyanine photoconductive material and adhesive resin material, polymer resin material, conductive resin material and lubricant are respectively subjected to preliminary crushing and refining treatment by the first mixer, and then subjected to ultrasonic crushing and refining treatment by the second mixer to obtain the corresponding first liquid material, second liquid material and third liquid material.
[0033] In specific implementation, 33% titanium dioxide and 67% conductive nylon are added to a V-type mixer. After preliminary crushing and refining, the mixture is placed in a multi-layer mixer for ultrasonic crushing and refining to obtain the first liquid material. 45% copper phthalocyanine and 55% pure polyethylene are added to a V-type mixer for preliminary crushing and refining, and then placed in a multi-layer mixer for ultrasonic crushing and refining to obtain the second liquid material. 32% high-molecular-weight resin PC, 64% polyethylene, and 4% silicon dioxide are added to a V-type mixer for preliminary crushing and refining, and then placed in a multi-layer mixer for ultrasonic crushing and refining to obtain the third liquid material.
[0034] S202, the first liquid material, the second liquid material and the third liquid material are dispersed using a disperser with first dispersion parameters to obtain a first optical waveguide material, a second optical waveguide material and a third optical waveguide material;
[0035] In specific implementation, the first liquid material, the second liquid material, and the third liquid material are respectively placed in a disperser for dispersion at a temperature of 20℃ to 40℃ (30℃ in this embodiment) for 7 days to obtain the first optical waveguide material, the second optical waveguide material, and the third optical waveguide material. The particle size of the first optical waveguide material is 300nm, the particle size of the second optical waveguide material is 2μm, and the particle size of the third optical waveguide material is 5μm. The concentration and viscosity of the liquids are checked, and coating treatment is performed according to the concentration and viscosity values. The coating is processed using automated production equipment.
[0036] S203, the first optical guide material is coated onto the OPC aluminum tube, and the coating is dried after coating the OPC aluminum tube to form the first coating;
[0037] S204, the second optical guide material is coated onto the OPC aluminum tube, and the OPC aluminum tube is dried after coating to form the second coating;
[0038] S205, the third photoconductive material is coated onto the OPC aluminum tube, and the OPC aluminum tube is dried after coating to form the third coating, so as to obtain a photosensitive drum containing photoconductive material.
[0039] In specific implementation, a first photoconductive material is coated onto an OPC aluminum tube, and the tube is dried after coating to form the first coating. A second photoconductive material is then coated onto the OPC aluminum tube, and the tube is dried after coating to form the second coating. A third photoconductive material is then coated onto the OPC aluminum tube, and the tube is dried after coating to form the third coating, thus obtaining a photosensitive drum containing photoconductive material. The coating concentration ranges for the first, second, and third photoconductive materials are 18–22 mol / L, and the coating viscosity ranges for all three materials are 35–45 mol / L. When the coating thickness is 0.8 μm–1.2 μm, the coating speed is 1–1.2 mm / s; when the coating thickness is 6–7 μm, the coating speed is 2.6–2.8 mm / s; and when the coating thickness is 30–36 μm, the coating speed is 15–20 mm / s.
[0040] Preferably, the coating concentration range of the first optical waveguide material is 20 mol / L and the coating viscosity range is 40 mol / L. When the coating thickness is 1 μm, the coating speed is 1 mm / s; when the coating thickness is 6 μm, the coating speed is 2.6 mm / s; and when the coating thickness is 30 μm, the coating speed is 15 mm / s. The parameters used for the second and third optical waveguide materials are the same as those used for the first optical waveguide material.
[0041] Specifically, an OPC support frame is used to transfer products during the product switching process. After liquid is applied to the aluminum tube, a drying operation is performed, which adopts low-temperature drying and high-temperature drying with a drying time of 2.5 to 3 seconds. The temperature range of the low-temperature drying is 40 to 60°C, and the temperature range of the high-temperature drying is 110 to 140°C. To better adapt to the temperature difference from the ambient temperature and prevent the temperature difference from affecting the surface quality of the product, the OPC aluminum tube rotates on its axis at a first preset rotation speed during drying.
[0042] Preferably, the temperature of low-temperature drying is 60°C, the temperature of high-temperature drying is 140°C, the drying time is 2.5s, and the first preset rotation speed is 2s per revolution.
[0043] In this embodiment, the qualification of the liquid formulation is checked. After the first coating is completed, the yield of the liquid formulation can be inspected by visual appearance, where the roughness and gloss of the appearance can reflect whether the liquid formulation is good: the finer the roughness, the better, and the brighter the gloss, the better (the coating thickness is detected by a film thickness meter, the photosensitivity test uses an electrical characteristic tester, and a surface roughness tester is used to measure the surface roughness of the coating to automatically inspect the product: first scan the surface image of the OPC product, and then compare it with the finished product image from R&D experiments). After the second coating is completed, the yield of the liquid formulation is inspected by the card insertion appearance, checking whether there are black spots, foreign matters, circular streaks, white lines, etc. on the entire coating. If none of these situations occur, the liquid formulation is considered qualified. After the third coating is completed, the yield of the liquid formulation is inspected by the card insertion appearance, checking whether there are atomization, bubbles, foreign matters, white lines, circular streaks, etc. on the entire coating. If none of these situations occur, the liquid formulation is considered qualified. Finally, the quality of the final liquid formulation is determined by checking the electrical properties and printing effect of OPC (the product name after the liquid coating is completed). If the electrical property Vs is greater than 795, the electrical property Vr is less than 50, and the sensitivity is between 0.12 and 0.23, the electrical properties are considered good. The OPC is installed in a laser printer for printing to check the printing effect. If the effect is clear, flawless, free of white stripes, and uniform in color, the liquid formulation is considered qualified. In addition, batch printing is used to test the long-term storage stability of the liquid quality: the higher the printing life, the better the liquid formulation.
[0044]
[0045] In summary, the method for preparing photoconductive materials for laser printing in the above embodiments of the present invention forms a first coating by selecting appropriate proportions of inorganic compounds and conductive polymer materials, forms a second coating by selecting appropriate proportions of phthalocyanine photoconductive materials and adhesive resin materials, and forms a third coating by selecting appropriate proportions of polymer resin materials, conductive resin materials and lubricants. The prepared photoconductive material has good electrical properties, good long-term preservation, and high printing quality and printing life.
[0046] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0047] The embodiments described above are merely illustrative of several implementation methods of this application, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the protection scope of this application. Therefore, the protection scope of this patent application should be determined by the appended claims.
Claims
1. A photoconductive material for laser printing, characterized in that, The material comprises a first coating, a second coating, and a third coating. The first coating comprises 33-37% by mass of an inorganic compound and 63-67% by mass of a conductive polymer material, dispersed at a first particle size using nanotechnology. The second coating comprises 35-45% by mass of a phthalocyanine photoconductive material and 55-65% by mass of an adhesive resin material, dispersed at a second particle size. The third coating comprises 32-38% by mass of a polymer resin material, 58-64% by mass of a conductive resin material, and 4% by mass of a lubricant, dispersed at a third particle size. The first particle size is 200~300nm, the coating thickness of the first coating is 3~6μm, the inorganic compound includes any one of titanium dioxide, zinc oxide, and tungsten oxide, and the conductive polymer material includes any one of conductive nylon, polyacrylamide, and polypyrrole. The second particle size is 1~2μm, the coating thickness of the second coating is 0.8~2μm, the phthalocyanine-based optical guide material includes any one of copper phthalocyanine, nickel phthalocyanine, zinc phthalocyanine, cobalt phthalocyanine, and iron phthalocyanine, and the adhesive resin material is any one of polyvinyl alcohol and conductive PC; The third particle size is 2~5μm, the coating thickness of the third coating is 30~40μm, and both the polymer resin material and the conductive resin material include any one of the following: polymer resin PC, polyethylene, polymer PAM, polyacrylamide, melamine, and formaldehyde resin.
2. The optical guide material for laser printing according to claim 1, characterized in that, The lubricant includes silicon dioxide.
3. A method for preparing a photosensitive drum containing a photoconductive material, wherein the photoconductive material is the photoconductive material according to any one of claims 1-2, characterized in that, The preparation method includes: The inorganic compound, conductive polymer material, phthalocyanine photoconductive material, adhesive resin material, polymer resin material, conductive resin material, and lubricant are initially crushed and refined by the first mixer, and then ultrasonically crushed and refined by the second mixer to obtain the corresponding first liquid material, second liquid material, and third liquid material. The first liquid material, the second liquid material, and the third liquid material are dispersed using a disperser with first dispersion parameters to obtain a first optical waveguide material, a second optical waveguide material, and a third optical waveguide material. The first optical guide material is coated onto the OPC aluminum tube, and the coating is dried after coating the OPC aluminum tube to form the first coating. The second optical guide material is coated onto the OPC aluminum tube, and the OPC aluminum tube is dried after coating to form the second coating. The third photoconductive material is coated onto the OPC aluminum tube, and the OPC aluminum tube is dried after coating to form the third coating, so as to obtain a photosensitive drum containing the photoconductive material.
4. The preparation method according to claim 3, characterized in that, The first mixer is a V-type mixer, the second mixer is a multi-layer mixer, and the first dispersion parameters include a temperature of 20℃~40℃ and a dispersion time of 7 days.
5. The preparation method according to claim 3, characterized in that, The coating concentration range of the first, second, and third optical waveguide materials is 18-22 mol / L, and the coating viscosity range is 35-45 mol / L. When the coating thickness is 0.8 μm-1.2 μm, the coating speed is 1-1.2 mm / s; when the coating thickness is 6-7 μm, the coating speed is 2.6-2.8 mm / s; and when the coating thickness is 30-36 μm, the coating speed is 15-20 mm / s.
6. The preparation method according to claim 3, characterized in that, The drying process employs both low-temperature drying and high-temperature drying, with a drying time of 2.5 to 3 seconds. The temperature range for low-temperature drying is 40 to 60 degrees Celsius, and the temperature range for high-temperature drying is 110 to 140 degrees Celsius. The OPC aluminum tube rotates at a first preset rotation speed during the drying process.
Citation Information
Patent Citations
Three-layer coating process and photosensitive drum prepared by adopting same
CN102998917A
Negative electricity three-layer OPC drum
CN113820932A